THE ROLE OF SCIENTIFIC CIRCLES IN IMPROVING THE QUASIPROFESSIONAL ACTIVITIES OF FUTURE BIOLOGY TEACHERS - Raupova Mehrinigor Khaidarovna (Scholar Express Journal, 2022)
The article describes the activities of the "Quasi-professional activity" circle and its role in the formation of professional characteristics of students. The role of quasi-professional activities in the step-by-step professional training of future biology teachers is shown. Consideration of these tasks is explained by the author's belief that the quasi-professional model of education can be fully implemented not only in classrooms, but also in other practice-oriented educational areas of higher education
Keywords: Quasi-professional activities; modeling; become a; project